Association of time on outcome after intravenous thrombolysis in the elderly in a telestroke network. (January 2016) - Zerna, Charlotte; Siepmann, Timo; Barlinn, Kristian; Kepplinger, Jessica; Pallesen, Lars-Peder; Puetz, Volker; Bodechtel, Ulf
Background: Recent studies showed that the safety and benefit of early intravenous (IV) thrombolysis on favourable outcomes in acute ischemic stroke are also seen in the elderly. Furthermore, it has shown that age increases times for pre- and in-hospital procedures. We aimed to assess the applicability of these findings to telestroke. Methods: We retrospectively analysed 542 of 1659 screened consecutive stroke patients treated with IV thrombolysis in our telestroke network in East-Saxony, Germany from 2007 to 2012. Outcome data were symptomatic intracranial hemorrhage (sICH) by ECASS-2-criteria, survival at discharge and favourable outcome, defined as a modified Rankin scale (mRS) of 0–2 at discharge. Results: Thirty-three percent of patients were older than 80 years (elderly). Being elderly was associated with higher risk of sICH ( p  = 0.003), less favourable outcomes ( p  = 0.02) and higher mortality ( p  = 0.01). Using logistic regression analysis, earlier onset-to-treatment time was associated with favourable outcomes in not elderly patients (adjusted odds ratio (OR) 1.18; 95% CI 1.03–1.34; p  = 0.01), and tended to be associated with favourable outcomes (adjusted OR 1.13; 95% CI 0.92–1.38; p  = 0.25) and less sICH (adjusted OR 0.88; 95% CI 0.76–1.03; p  = 0.11) in elderly patients. Age caused no significant differences in onset-to-door-time ( p  = 0.25), door-to-treatment-time ( p  = 0.06) or onset-to-treatment-time ( p  = 0.29). Conclusion: Treatment time seems to be critical for favourable outcome after acute ischemic stroke in the elderly. Age is not associated with longer delivery times for thrombolysis in telestroke.